Perianal fistulas characterization using magnetic resonance imaging. Qatar Cuban Hospital, 2017-2023 - Rolando Dornes Ramon; Yordany Vázquez Mora; Yunelkys Martínez Castro; Isbelys Flatts Segundo; Aimé Alberna Cardoso (Medisur)
Foundation: the suppurative inflammatory disease, known as perianal fistula, is the result of multiple interrelated factors. The appropriate typing of these lesions using magnetic resonance imaging allows planning, according to the degree of complexity observed, the most indicated surgical treatment. Objective: to characterize perianal fistulas using magnetic resonance imaging findings. Methods: an observational, descriptive and cross-sectional study was carried from January 2017 to May 2023, in the Qatar Cuban Hospital Imaging Department. The sample consisted of 37 patients with clinical suspicion of perianal fistula, referred by the General Surgery service, which underwent high-field magnetic resonance imaging to confirm. Demographic studied variables were, as well as personal pathological history, degree of injury, clinical manifestations, time location and length of the fistulous tract. Results: there was the male sex predominance and the age group of 30-44 years (51.4%). Simple intersphincter fistula (grade I) was the most common, followed by intersphincter fistula with associated abscess (grade II). The predominant personal pathological history was hidranetitis suppurativa (35.1%). Conclusions: high-field magnetic resonance imaging allowed the evaluation, diagnosis and characterization of perianal fistulas, as well as their associated complications. Grade I and II fistulas predominated; and hidradenitis suppurativa, diabetes mellitus, previous fistula and tuberculosis as a personal pathological history.